(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To evaluate the outcomes of total hip arthroplasty (THA) using a dual mobility implant. Methodology: A cohort of 49 patients, aged 35 to 80 years and including both genders, who were scheduled for THA for various indications, were enrolled in this study. Patients underwent both clinical and radiographic evaluations prior to the surgery. The dual mobility implant was utilized during THA. Follow-up assessments were conducted three months postoperatively to monitor for any incidents of dislocation. The study spanned from [start date] to [end date] and received ethical approval under the reference number [ethical approval reference number]. Results: Out of the 49 patients, 32 (65.3%) were male, resulting in a male-to-female ratio of 2:1. The mean age of the patients was 61.00 ± 10.51 years. The mean preoperative Harris Hip Score was 49.04 ± 7.33, which improved significantly to 88.45 ± 8.58 postoperatively (p < 0.001). There were no dislocations observed during the follow-up period. Conclusion: The study found a statistically significant improvement in Harris Hip Scores from preoperative to postoperative assessments, with no dislocations occurring following THA using a dual mobility implant.